Dose-dependent effects of enzyme replacement therapy on skeletal disease progression in mucopolysaccharidosis VII dogs - Rahul Gawri; Yian Khai Lau; Gloria Lin; Snehal S. Shetye; Chenghao Zhang; Zhirui Jiang; Khaled Abdoun; Carla R. Scanzello; Stephanie Y. Jo; Wilfried Mai; George R. Dodge; Margret L. Casal; et al. (Molecular Therapy: Methods & Clinical Development, 2023)
Mucopolysaccharidosis (MPS) VII is an inherited lysosomal storage disorder characterized by deficient activity of the enzyme β-glucuronidase. Skeletal abnormalities are common in patients and result in diminished quality of life. Enzyme replacement therapy (ERT) for MPS VII using recombinant human β-glucuronidase (vestronidase alfa) was recently approved for use in patients; however, to date there have been no studies evaluating therapeutic efficacy in a large animal model of MPS VII. The objective of this study was to establish the effects of intravenous ERT, administered at either the standard clinical dose (4 mg/kg) or a high dose (20 mg/kg), on skeletal disease progression in MPS VII using the naturally occurring canine model. Untreated MPS VII animals exhibited progressive synovial joint and vertebral bone disease and were no longer ambulatory by age 6 months. Standard-dose ERT-treated animals exhibited modest attenuation of joint disease, but by age 6 months were no longer ambulatory. High-dose ERT-treated animals exhibited marked attenuation of joint disease, and all were still ambulatory by age 6 months. Vertebral bone disease was recalcitrant to ERT irrespective of dose. Overall, our findings indicate that ERT administered at higher doses results in significantly improved skeletal disease outcomes in MPS VII dogs.